Design and experiment of a novel intelligent device suitable for automation vegetable plug seedling - Qiu Haifei; Nie Zhike; Chen Xiandong; Lv Bo; Zhang Yifan; Li Feiyang; Zhang Jiajun (PLoS ONE, 2025)
To tackle the challenges of high manual labor intensity and low efficiency in traditional vegetable plug seedling processes, this study developed an automated mechanical device through innovative design, dynamic simulation, single-chip development, and prototype testing. The device integrates precision seeding technology based on the synchronized motion control of ball screws and crank sliders, which improves the qualification rate of plug sowing to 98% by “one hole one seed” sowing, and also minimizes seed waste and reduces planting costs. Automated processes like hole pressing, sowing, soil covering, fertilizing, and watering are achieved through innovative design and functional integration, ensuring efficient and high-quality plug seedling production. Additionally, real-time monitoring of vegetable cultivation parameters, including seed type, quantity, planting depth, and environmental temperature and humidity, is facilitated by wireless WiFi, intelligent screens, and Alibaba Cloud, offering valuable technical insights for the digital and intelligent advancement of new vegetable plug seedling machinery.